P16 Vascular repair and regeneration are improved with reduced expression of the insulin-like growth factor-1 receptor in whole body insulin resistance. (26th October 2016) - Walker, Andrew MN; Yuldasheva, Nadira; Sengupta, Anshu; Mercer, Ben; Ali, Noman; Patel, Peysh A; Gatenby, V Kate; Smith, Jessica; Haywood, Natalie; Imrie, Helen; Galloway, Stacey; Mughal, Romana; et al.
Abstract : Rationale: Insulin resistance increases the risk of cardiovascular disease. Previous work from our department using mice haploinsufficient for either the IR (IRKO), IGF-1R (IGF-1RKO) or both receptors (DKO) showed that endothelial dysfunction caused by insulin resistance could be rescued by reducing IGF-1R expression. Whether there might also be an improvement in vascular repair and regeneration in this setting is unclear. Methodology: Weight curves and glucose and insulin tolerance tests were used for metabolic assessment. Denuding femoral artery injury was performed with angioplasty guidewires; repair was quantified in Evans Blue-perfused vessels at day 4. Hindlimb ischemia experiments involved left femoral artery ligation and excision, with contralateral sham surgery. Recovery was assessed weekly by laser Doppler. Flow cytometry was used to count circulating progenitor cells (CPCs) expressing Sca1/KDR. Data are expressed as mean (standard error) and compared using t-tests; * denotes p < 0.05. Results: Body weight was significantly lower in DKO than IRKO [area under curve (arbitrary units) 116 (2.1) vs 123 (2.4)* n = 15]. Glucose and insulin tolerance tests were similar in DKO and IRKO mice. The DKO group had superior re-endothelialisation after denuding femoral artery wire injury compared with IRKO [55 (4)% vs 46 (6)%* n = 8–14]. Recovery after induction of hindlimb ischemia was greatest in the DKO group [area under curve limb perfusion ratio (arbitrary units) 2.2 (0.11) vs 1.3 (0.08)* n = 12–19]. No difference was noted in CPC populations. Conclusion: Reducing IGF-1R expression improves vascular repair and regeneration in the context of whole-body insulin resistance. Further work will aim to elucidate the possible mechanisms for these observations.